Eyelash transplantation for the treatment of vitiligo associated eyelash leucotrichia - Manas Chatterjee (Journal of Cutaneous and Aesthetic Surgery, 2016)
Background: Eyelash leucotrichia is cosmetically disfiguring condition and remains a therapeutic challenge in successful management of vitiligo. Aims: To study the efficacy of eyelash transplantation in management of eyelash leucotrichia associated with vitiligo. Materials and Methods: Fifteen patients with eyelash leucotrichia were treated with follicular unit transplantation. Improvement in leucotrichia was evaluated using objective assessment. Results: Out of fifteen patients, good to excellent response was seen in 13 patients (86.67%), fair in one patient (6.66%) and poor in one patient (6.66%). Conclusion: Eyelash transplantation is safe and effective method for eyelash leucotrichia.